Inflammation mediated the effect of dietary fiber on depressive symptoms - Zhang, Ting; Cui, Xiao-mei; Zhang, Yu-ying; Xie, Tao; Deng, Yuan-jia; Guo, Fang-xi; Wang, Qi; Wu, Qing-feng; Dong, Ming-hua; Luo, Xiao-ting (Frontiers in Psychiatry, 2023)
Background & aims: Previous studies have shown that inflammation affects depressive symptoms. Dietary fiber may be associated with inflammation and depressive symptoms. We aimed to investigate the relationship between inflammation and depressive symptoms at different levels of dietary fiber intake and to explore whether dietary fiber affects depression through inflammation. Methods: A total of 8,430 National Health and Nutrition Examination Survey (NHANES) samples were collected between 2015 and 2018. Factor analysis was used to determine dietary patterns. Linear regression and logistic regression analysis were used to explore the relationship between nutrients, inflammation and depressive symptoms, and the mediation analysis was conducted by bootstrap method. Results: Factor 3 (dietary fiber and vitamins) was inversely associated with depressive symptoms and inflammation. Upper quartile of dietary inflammatory index (DII) scores and C-reactive protein (CRP) were associated with depressive symptoms compared with controls (DII: OR=1.851, 95%CI: 1.267-2.705; CRP: OR=1.737, 95%CI: 1.136-2.656). DII score and CRP were associated with the depressive symptoms in the group with low dietary fiber intake (DII: OR=2.736, 95%CI: 1.628-4.598; CRP: OR=2.092, 95%CI: 1.196-3.658), but this association was not found in participants with high dietary fiber intake. Mediating analysis showed that CRP partially mediated the effect of dietary fiber intake on depressive symptoms (βindirect=-0.0025, 95%CI: -0.0038 - -0.0013), and the mediated proportion was 10.5%. Conclusions: In this study, we found DII scores and CRP were not associated with depressive symptoms in participants with high dietary fiber intake, and inflammation partially mediates the effect of dietary fiber on depressive symptoms.